Pengaruh Pupuk Kandang Ayam dan Pupuk Majemuk NPK 16:16:16 pada Pertumbuhan dan Produksi Tanaman Sawi Hijau (Brassica chinensis var. parachinensis) - Eko Syahputra; Lily Novianty; Juhardi Sembiring (JURNAL AGROPLASMA, 2023)
Green mustard or often also called mustard meatball is a vegetable commodity that has good opportunities or prospects to be cultivated in urban areas using polybag media. Chicken manure contains a lot of N element which is very good for leaf growth. While compound fertilizer NPK 16:16:16 is perfect because it has immediate nutrients such as Nitrogen, Phospot and Potassium which these nutrients will stimulate plant growth. This study aims to determine whether there is an effect of giving chicken manure and compound fertilizer NPK 16:16:16 on the growth and production of mustard (brassica chinensis var. Parachinensis). This study used a randomized block design with 2 treatment factors and 3 replications. Which factor I consists of 4 levels A0 = No chicken manure A1 = Chicken manure 10 tons/ha (equivalent to 15 g/polybag), A2 = Chicken manure 20 tons/ha (equivalent to 30 g/polybag), A3 = Chicken manure 30 tons/ha (equivalent to 45 g/polybag) while the second factor consists of 3 levels, namely N0 without NPK fertilizer N1 = NPK fertilizer 450 kg/ha (equivalent to 0.675 g/polybag) N2 = NPK fertilizer 900 kg/ha (equivalent to 1.35 g/polybag), resulting in 12 combinations. Furthermore, the research parameters were seen from plant height, number of leaves, leaf area, root dry weight, root wet weight, biomass weight of the sample, wet weight of planting and root volume. So that the research results from the parameters seen there are only a few parameters that have a very significant effect such as leaf width and plant height. While the number of leaves and biomass weight of the sample had no effect, but not significant, while other parameters such as wet weight of planting, wet weight of roots, dry weight of roots and root volume had no effect, therefore to get more optimal results it is recommended to conduct further research. Key words : Chicken manure, compound fertilizer NPK 16:16:16, green mustard